Occipital nerve stimulation in medically intractable, chronic cluster headache. The ICON study: Rationale and protocol of a randomised trial. (November 2013) - Wilbrink, Leopoldine A; Teernstra, Onno PM; Haan, Joost; van Zwet, Erik W; Evers, Silvia MAA; Spincemaille, Geert H; Veltink, Peter H; Mulleners, Wim; Brand, Ronald; Huygen, Frank JPM; Jensen, Rigmor H; Paemeleire, Koen; et al.
Background: About 10% of cluster headache patients have the chronic form. At least 10% of this chronic group is intractable to or cannot tolerate medical treatment. Open pilot studies suggest that occipital nerve stimulation (ONS) might offer effective prevention in these patients. Controlled neuromodulation studies in treatments inducing paraesthesias have a general problem in blinding. We have introduced a new design in pain neuromodulation by which we think we can overcome this problem. Methods/design: We propose a prospective, randomised, double-blind, parallel-group international clinical study in medically intractable, chronic cluster headache patients of high- versus low-amplitude ONS. Primary outcome measure is the mean number of attacks over the last four weeks. After a study period of six months there is an open extension phase of six months. Alongside the randomised trial an economic evaluation study is performed. Discussion: The ICON study will show if ONS is an effective preventive therapy for patients suffering medically intractable chronic cluster headache and if there is a difference between high- and low-amplitude stimulation. The innovative design of the study will, for the first time, assess efficacy of ONS in a blinded way.